Effect of denture adhesive on the micro-organisms in vivo - ÖZKAN, YASEMİN (WILEY-BLACKWELL, 2012)
Background: Denture adhesives increase the retention and stability of dentures in edentulous patients, especially in cases where salivary flow is impaired or in the management of traumatised oral mucosa. Objectives: The effect of a denture adhesive on the oral flora at different time intervals. Method: Thirty denture-wearing patients were involved in this study. While half of the group received a denture adhesive, the other half did not. At baseline, 1 and 2 months after delivering the dentures, smear samples were obtained from the saliva, palate and the dentures. Candida albicans, Candida krusei, Candida glabrata, Candida spp., Staphylococcus aureus, Moraxella catarrhalis, a-haemolytic streptococci, b-haemolytic streptococci, Pneumococcus aureus, S. anginosus, S. intermedius, S. constellatus, S. sanguis, S. gordonii, S. mitis, S. mutans, S. salivarius, and yeasts were investigated. The data were statistically analysed using ANOVA and repeated measures. Results: Most types of the micro-organisms were not seen and could not be analysed statistically except ahaemolytic streptococci and C. albicans. No statistically significant difference was found for a-haemolytic streptococci and C. albicans in saliva, palate and the denture at all time intervals. Conclusions: Prolonged use of the denture adhesive tested up to 2 months did not yield to increase in micro-organisms of the oral flora.
Keywords: Candida albicans; denture adhesive; denture micro-organisms; RETENTION; ATTITUDES